ARTIFICIAL INTELLIGENCE (AI) IN NIGERIAN EDUCATION: A NECESSITY FOR SCHOOL RECORDS MANAGEMENT - Kwashabawa, Bala Bakwai; KOLAPO, PETER OLUWAYOMI; ONAOLAPO, SAFURAT AHMED; ADENIRAN, DEBORAH OPEYEMI (Sokoto Educational Review, 2025)
The Nigerian education system faces persistent challenges in school records management at both ministry and school levels, necessitating a prompt and sustainable solution. Effective management of this data is critical, as high-quality, timely, and reliable information underpins sound decisions about future planning, current activities, and monitoring. Thus, a robust Management Information System (MIS) is essential to generate the necessary data for informed decision-making. MIS, a synergy of computer, communication, and electronics, enables the acquisition, processing, storage, and dissemination of various forms of information—vocal, textual, pictorial, and numerical—using micro-electronic equipment. The adoption of Information and Communication Technology (ICT) facilitates rapid information distribution, reflecting how ICT has reshaped society, including the education sector. Integrating Artificial Intelligence (AI) into school records data management offers a revolutionary path forward, enabling educational institutions to streamline processes, gain deeper insights into academic performance, improve decision-making, and ultimately enhance student outcomes by leveraging advanced AI technologies. DOI: https://doie.org/10.10318/SER.2025788350